Investigation of the Catalytic Properties of Aluminum Oxide (Al2O3) and Pyrite (FeS2) Using Thermodynamic and Kinetic Parameters - Aigul T. Ordabaeva; Zainulla M. Muldakhmetov; Mazhit G. Meiramov; Sergey V. Kim; Shuga B. Kasenova; Serik D. Fazylov (Molecules)
The kinetics of anthracene hydrogenation was studied using the method of equilibrium kinetic analysis. To determine the diffusion–kinetic characteristics, anthracene hydrogenation was performed at different temperatures (648 K, 673 K, 698 K), at a hydrogen pressure of 3 MPa in the presence of a mixture of pyrite (FeS2) and aluminum oxide (Al2O3) taken at a ratio of 1:1. Chromatographic analysis of anthracene hydrogenation products showed the presence of 9,10-dihydroanthracene (DHA), 1,2,3,4-tetrahydroanthracene (THA), methylnaphthalene (MN), naphthalene (H) and other unidentified compounds. In order to preserve the material balance, a total hydrogenation reaction of anthracene, up to 9,10-dihydroanthracene, was proposed as characterized by the highest rate in the presence of pyrite-based catalysts and aluminum oxide. Calculations of the degrees of rotation of anthracene, reaction constants, and Gibbs energy have shown that with increasing temperature, the reaction becomes more thermodynamically advantageous. Based on the obtained data, Arrhenius dependences were constructed, which made it possible to calculate the activation energies of direct (39.4 kJ/mol) and reverse (13.04 kJ/mol) reactions. Thus, based on the calculations performed, it was found that the process of anthracene hydrogenation in the presence of a mixture of pyrite and aluminum oxide proceeds mainly in the diffusion region.